Some characteristic properties of the weighted particular Schur polynomial mean. (19th July 2019) - Zhang, Zhi‐Hua; M. Srivastava, Hari
Abstract : This paper provides some characteristic properties of the weighted particular Schur polynomial mean of several variables. In addition, an elementary proof of an important inequality involving the weighted particular Schur polynomial mean is given. Various related results involving a family of the Schur polynomials, symmetric polynomials, and other associated polynomials, together with the potential for their applications, are also considered.